Innovative marketing strategy in the agribusiness sector to increase farmers' income - Tri Waluyo (Journal Arbitrase : Economy, Management and Accounting, 2024)
This research aims to analyze and identify innovative marketing strategies that can be implemented in the agribusiness sector to increase farmers' income. Economic growth and farmer welfare are important factors in the development of the agricultural sector. This research uses a qualitative approach with descriptive methods. The research results show that innovative marketing strategies in the agribusiness sector can be effective in increasing consumer understanding about product quality, added value and sustainable agricultural practices. The application of digital technology, strong branding, social marketing campaigns, network building, product-based experience, flexible pricing strategies, and training for farmers have made a positive contribution to increasing farmer income. The use of online platforms increases product accessibility, while branding and product differentiation create a positive image and differentiate the brand from competitors. Social media and educational campaigns support consumer engagement, while networks and partnerships strengthen distribution and farmer training. Product-based experiences and flexible pricing strategies stimulate consumer interest and increase sales. Training farmers on modern marketing and sustainable farming practices improves the skills and competitiveness of the agribusiness sector as a whole.